Update on Femoroacetabular Impingement: What Is New, and How Should We Assess It? - Sutter, Reto; Pfirrmann, Christian W. A. (Seminars in Musculoskeletal Radiology, 2017)
It is almost 20 years since the concept of femoroacetabular impingement (FAI) was introduced, and by now a large number of orthopaedic surgeons, sports physicians, and radiologists have implemented this concept in clinical practice, as is evident in the steady rise in the number of patients diagnosed and treated for FAI. However, this trend has been accompanied by some criticism and concerns about overdiagnosing FAI. Imaging continues to play a crucial part in the evaluation of patients with suspected FAI. This review looks at the current state of FAI: Which parts of the FAI concept have become widely accepted, which ideas have been abandoned, and how should we assess patients with suspected FAI today? Although cam- and pincer-type morphology remain two central pillars of the FAI concept, the important role of abnormal femoral torsion in the development of FAI has now been recognized. High-level sports activities during skeletal maturation have been proven to increase the risk of developing FAI.
Keywords: femoroacetabular impingement; cam; pincer; femoral torsion